2001
DOI: 10.1161/hy1101.093426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antisense Oligodeoxynucleotide Targeting of the α 2B -Adrenergic Receptor Messenger RNA in the Central Nervous System

Abstract: Abstract-The results of previous studies with genetically engineered mice have suggested that an intact central ␣ 2B -adrenergic receptor (␣ 2B -AR) subtype mediates the development and maintenance of salt-induced hypertension. In the present study, we sought to further define the role of this receptor by injecting antisense oligodeoxynucleotides (AS-ODNs), targeting a selected sequence of the ␣ 2B -AR mRNA, into the lateral cerebral ventricle of rats that had undergone prior subtotal nephrectomy and dietary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
(40 reference statements)
1
20
0
1
Order By: Relevance
“…This hypothesis is supported by the finding that acute hypertensive responses to an intravenous infusion of hypertonic saline were absent in anephric (to exclude renal effects) ␣ 2B -AR (ϩ/Ϫ) mice, whereas in wild-type mice, pressure rose by 15 mmHg (127). This hypothesis is supported by recent findings in rats, in which local injection of antisense oligodeoxynucleotides targeted to ␣ 2B -ARs inhibited the induction of salt-induced hypertension (100). Thus the increased susceptibility of ␣ 2A -AR-knockout mice to homeostatic challenges may, in part, be mediated by compensatory actions of central ␣ 2B -ARs.…”
Section: ␣2-adrenergic Receptorssupporting
confidence: 58%
“…This hypothesis is supported by the finding that acute hypertensive responses to an intravenous infusion of hypertonic saline were absent in anephric (to exclude renal effects) ␣ 2B -AR (ϩ/Ϫ) mice, whereas in wild-type mice, pressure rose by 15 mmHg (127). This hypothesis is supported by recent findings in rats, in which local injection of antisense oligodeoxynucleotides targeted to ␣ 2B -ARs inhibited the induction of salt-induced hypertension (100). Thus the increased susceptibility of ␣ 2A -AR-knockout mice to homeostatic challenges may, in part, be mediated by compensatory actions of central ␣ 2B -ARs.…”
Section: ␣2-adrenergic Receptorssupporting
confidence: 58%
“…Moreover, various experiments on salt-induced hypertension in mice deficient in one of the three ␣ 2 -adrenoceptor subtypes (Makaritsis et al, 1999a(Makaritsis et al, ,b, 2000 allowed the suggestion that adrenergically mediated hypertension depends on the central ␣ 2B -adrenoceptors. The validity of this hypothesis is further supported by a recent study showing that intracerebroventricular microinjection of antisense-oligonucleotides targeting a specific sequence of the ␣ 2B -adrenoceptor gene in salt-sensitive rats lowered blood pressure (Kintsurashvili et al, 2001). Therefore, it seems likely that the up-regulation of hypothalamic ␣ 2B -adrenoceptor gene expression that we observed only in the hypertensive cafeteria diet-fed rats participates in the maintenance of the hypertensive state.…”
Section: Downloaded Frommentioning
confidence: 78%
“…In contrast, the ␣ 2B -adrenoceptor mediates the ␣ 2 -agonist-induced increase in blood pressure (Link et al, 1996). Moreover, from a subsequent series of studies on salt-induced hypertension in ␣ 2 -adrenoceptor subtype-deficient mice (Makaritsis et al, 1999a,b), or by using the antisense strategy (Kintsurashvili et al, 2001), it has been suggested that the adrenergically mediated hypertension depends on the central ␣ 2B -adrenoceptor subtype. In contrast with other brain structures, hypothalamus is the area in which the ␣ 2B -adrenoceptor gene is the subtype most expressed (Tavares et al, 1996).…”
mentioning
confidence: 99%
“…However, activation of both α 2B -and α 2C -ARs also elicit central effects. Mice with targeted inactivation of the α 2B -AR are resistant to the development of salt-sensitive hypertension [10,11] and α 2B -AR antisense lowers BP in hypertensive rats [12,13]. Mice deficient in α 2C -AR have an augmented startle response and sensorimotor gating deficits, whereas overexpression of the α 2C -AR increases the latency to the startle reflex and improves learning and memory [14,15].…”
Section: Central α 2 -Arsmentioning
confidence: 99%